НОВАЯ СПЕЦИАЛИЗИРОВАННАЯ ПРОЛАЦЕРТИЛИЯ (REPTILIA: ARCHOSAUROMORPHA) ИЗ НИЖНЕГО ТРИАСА ОРЕНБУРГСКОЙ ОБЛАСТИ - Сенников А.Г. (My University, 2005)
A new large specialized prolacertilian, Vritramimosaimis dzerzhinskii gen. et sp. nov., from the Lower Triassic of the Rassypnaya locality (Orenburg Region, European Russia) and new specimens of the Middle Triassic prolacertilian Malutinisuchus grains are described. The diversity, phylogeny, systematics, and geographical and stratigraphie distribution of prolacertilians are discussed.
Keywords: Мезозой::Триасовая